Magnetism and thermomechanical properties in Si substituted MnCoGe compounds - Abdul Rahman, Abdul Rashid; Md Din, Muhamad Faiz; Wang, Jianli; Hassan, Muhammad Zahir; Suhaimi, Nur Sabrina; Idris, Nurul Hayati; Dou, Shi Xue; Ismail, Mohammad; Jusoh, Mohd Taufik (MDPI AG, 2021)
MnCoGe-based compounds have been increasingly studied due to their possible large magnetocaloric effect correlated to the magnetostructural coupling. In this research, a comprehensive study of structure, magnetic phase transition, magnetocaloric effect and thermomechanical properties for MnCoGe1−xSix is reported. Room temperature X-ray diffraction indicates that the MnCoGe1−xSix (x = 0, 0.05, 0.1, 0.15 and 0.2) alloys have a major phase consisting of an orthorhombic TiNiSi-type structure with increasing lattice parameter b and decreasing others (a and c) with increasing Si concentration. Along with M-T and DSC measurements, it is indicated that the Tc value increased with higher Si concentration and decreased for structural transition temperature Tstr. The temperature dependence of the magnetization curves overlaps completely, indicating that there is no thermal hysteresis, and it is shown that the transition is the second-order type. It is also shown that the decreased magnetization on the replacement of Si for Ge decreases the value of −ΔSM from −ΔSM~8.36 J kg−1 K−1 at x = 0 to −ΔSM~5.49 J kg−1 K−1 at x = 0.2 with 5 T applied field. The performed Landau theory has confirmed the second-order transition in this study, which is consistent with the Banerjee criterion. The magnetic measurement and thermomechanical properties revealed the structural transition that takes place with Si substitution of Ge.